The influence of tumor heterogeneity on sensitivity of EGFR-mutant lung adenocarcinoma cells to EGFR-TKIs - Sun, Li; Li, Yao-Yong; Ma, Jie-Tao; Zhang, Shu-Ling; Huang, Le-Tian; Han, Cheng-Bo (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: Studies have shown that extensive genetic or spatial heterogeneity is present within tumors. The present study explored the influence of heterogeneous cells in the tumor microenvironment (TME) on the sensitivity of EGFR-mutant lung adenocarcinoma cells to EGFR-TKIs and further investigated associated molecular mechanisms. Methods: Tumor heterogeneity was simulated using transwell co-culture technique with H1975, A549 or MRC-5 cells grown in the upper chambers and PC-9 cells cultured in the bottom chamber. Each co-culture system was grouped based on different proportions of cells in the upper and lower chambers (from 1% to 300%), and each group was subdivided into erlotinib treatment group (erlotinib+) and erlotinib non-treatment group (erlotinib−). The viability of PC-9 cells was analyzed by CCK-8; HGF, IGF-1 and TGF-α were determined by ELISA; MET amplification was detected by qRT-PCR, and the relevant proteins were detected by Western blot. Results: The viability of PC-9 cells increased with increased proportion of A549/PC-9 or MRC-5/PC-9 cells from 1% to 300%. HGF increased with increased proportion of H1975 cells from 1% to 300%. In all three co-culture systems, TGF-α production in the erlotinib+ subgroup was significantly lower than that in erlotinib- subgroup, and phosphorylated AKT protein showed an ascending tendency with the increased proportion of upper chamber cells relative to PC-9 cells from 1% to 300%. H1975 cells could induce MET amplification of PC-9 cells. MRC5 cells inhibited MET amplification. Conclusions: Tumor heterogeneity partially accounts for the resistance of EGFR-mutant lung adenocarcinoma cells to EGFR-TKIs. The possible mechanisms may be related to AKT signaling pathways activated by growth factors, which are secreted by heterogeneous cells in the TME under the pressure of EGFR-TKIs.